Asuhan Keperawatan Pada Ny M dengan Penumonia - Nabila Naswa; Mike Asmaria; Hilma Yessi; Linda Marni (Jurnal Keperawatan Medika, 2026)
Pneumonia is a lung infection that is easily transmitted through droplets when coughing or sneezing. Worldwide, pneumonia causes around 6.3 million deaths, with 92% of cases occurring in Asia and Africa. And the diagnosed incidence of pneumonia in Indonesia reached 10.8% with a total of 877,531 cases. In RSUD Prof. H. Muhammad Yamin SH Pariaman, 89 cases of pneumonia were recorded. At At RSUD Prof. H. Muhammad Yamin SH Pariaman, 89 cases of pneumonia were recorded. This study aims to provide nursing care to Mrs. M, with pneumonia. The method used is a case study with a surgical medical nursing assessment approach, through interviews and direct observation. The research was conducted in the pulmonary inpatient room on February 20 to February 24, 2025 to see or recognize problems in Mrs. M. Age 60 years with a medical diagnosis of pneumonia. Nursing problems found include ineffective airway clearance, ineffective breathing patterns, nutritional deficits, constipation, activity intolerance and self-care deficits. Intervention and implementation carried out, namely airway management and respiration monitoring. With the results of the evaluation of ineffective airway clearance not resolved, ineffective breathing patterns, nutritional deficits, activity intolerance resolved on day 4 and constipation problems resolved on day 5. Advice given to patients regarding increasing fluid intake, recommending optimal rest, maintaining personal and environmental hygiene, managing a nutritious diet, increasing endurance, taking drugs according to doctor's recommendations and routinely controlling health care facilities.